Uji Efektivitas Beberapa Ekstrak Daun Tanaman terhadap Populasi Ulat Daun Kubis (Plutella xylostella L.) pada Tanaman Kubis di Lapang - BUDARTINI, NI KADEK; YULIADHI, KETUT AYU; SRITAMIN, MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Effectivity of Some Extract to Diamonback Moth (Plutella xylostella) Population On Cabbage Plant The research was conducted in November 2017 to February 2018 at Candikuning Village, Baturiti District, Tabanan Regency. The aim of this research is to observe effectiveness some extract on larvae of Diamonback Moth (Plutella xylostella) population on cabbage plant. Plant extract materials used in this experiment were leaf of Chromolaena odorata, Lantana camara, Tithonia diversifolia and Nicotiana tabacum. Process of extracting at Laboratory of Genetic Resources and Molecular Biology Faculty of Agriculture Udayana University. This research uses Randomized Block Design (RBD) with 4 treatment of leaf extract at 10% concentration and 1 without treatment (kontrol), there treatments was replicate 5 times. Observations were made on cabbage plants one week after planting and before application. Subsequent observations were conducted weekly, up to harvest by calculating the population larvae of Plutella xylostella. Testing of four types of plant leaf extracts showed the following results: Each of C. odorata leaf extract, L. camara, T. diversifolia, and N. tabacum used as research material had different potential in suppressing P. xylostella populations . Application of C. odorata and T. diversifolia leaf extracts was able to suppress P. xylostella populations faster than other treatments. The weight of cabbage crop on treatment of C. odorata was higher than that of other treatments and the quality of crop in all four types of extract showed quality category 2.